Model Pembelajaran Online Maharah Al- Kalam di Pusat Kursus Bahasa Arab Pondok “ Takallam” Pare Kediri Jawa Timur - Aidah Novianti Putri; Muhammad Zaenuri (Sekolah Tinggi Agama Islam Syaichona Moh. Cholil Bangkalan, 2022)
The selection of online learning models, especially for students, shows that the application of learning speaking skills is said to be unable to function perfectly without the formation of an active component and a linguistic environment. In addition, most of the Arabic language activists also have difficulty developing speaking skills due to space and time constraints. But in essence, language environments can be created not only through direct learning interactions, but also through distance learning programs. Therefore, one of the alternative learning methods that they can take to further develop their speaking skills is to take several online Arabic courses through informal learning institutions at the Takallam Institute of Arabic Language Course, Pare Kediri, East Java. The researcher used this research with descriptive and qualitative research types. This research was conducted at the Takallam Institute of Arabic Language Course in Pare Kediri, East Java. The subject of this research is a tutor or online class teacher at the Takallam Institute of Arabic Language Course at Pare Kediri, East Java. Meanwhile, the informants in this study were the director of the Takallam Institute of Arabic Language Course Institute Pare Kediri, East Java and participants of online class learning. The data collection methods that researchers use to obtain the data needed in writing this research, namely the method of observation, interviews and documentation. Test the validity of the data through source triangulation, technical triangulation, and temporal triangulation. While the data analysis technique was carried out in different stages, namely analysis before going into the field, data reduction, data presentation, and drawing conclusions. The results show that the online learning model of speaking skills at the Takallam Institute of Arabic Language Course in Pare Kediri, East Java, can run smoothly and inject the purpose of teaching speaking skills, meaning that participants can understand and practice speaking Arabic fluently. Learning speaking skills is carried out with the online maharah kalam learning model at the Takallam Institute Arabic Language Course Institute, Pare Kediri, East Java and is a type of direct learning model by applying the special